2016
DOI: 10.3139/113.110415
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Microbial Communities in Household Dishwashers in Germany

Abstract: The proper cleaning of used dishes provides an essential means to maintain a sufficient hygiene level on food contact surfaces. However, little is known on the microbiological quality of domestic dishwashers themselves, especially in relation to consumer habits. This study investigated dishwashers in German households to analyse the number and composition of microbial colonisers and their putative impact on dishwashing hygiene. Although the microbiological status of dishwashers appeared to depend on multiple f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Therefore, determining the influence of a specific parameter on the microfungi survival and development is complicated. The relationship between temperature (the only variable factor during the washing cycle) and the presence of microorganisms in dishwashers was shown by Brandt et al [60] and Brandt and Dirk [61]. As the temperature increased, yeast counts decreased, indicating an adverse effect of energy-saving measures on appliance hygiene.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, determining the influence of a specific parameter on the microfungi survival and development is complicated. The relationship between temperature (the only variable factor during the washing cycle) and the presence of microorganisms in dishwashers was shown by Brandt et al [60] and Brandt and Dirk [61]. As the temperature increased, yeast counts decreased, indicating an adverse effect of energy-saving measures on appliance hygiene.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, more tests with different dishwashers have to be performed and the behaviour of more test micro‐organisms should be evaluated in future to give a picture of the current situation. Nevertheless, numerous studies in different household appliances have shown that the hygiene status of household dishwashers must be considered quite good in general (Brands and Bockmühl ; Brands et al ), biofilms have been detected (Zalar et al ; Babič et al ; Nix et al ; Savage et al ; Egert ; Rehberg et al ; Raghupathi et al ; Zupančič et al ). However, dishwashing hygiene must be constantly observed since some micro‐organisms might be able to survive dishwashing cycles, should future developments in water and energy saving lead to a shift in the parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Es gibt Studien, die belegen, dass eine zuverlässige Keimreduktion auch in sog. Hygienespülprogrammen nicht von jedem Gerät erreicht wird [24,25]. Vielmehr könnte es zu einer neuen Kontamination der TK mit obligat pathogenen Mikroorganismen kommen.…”
Section: Merkeunclassified